2022
DOI: 10.7189/jogh.12.10011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of breastfeeding and complementary feeding for management and prevention of childhood diarrhoea in low- and middle-income countries

Abstract: Background Early and exclusive breastfeeding have been shown to protect young infants from all-cause and diarrhoea-related mortality. Ideally breastfeeding should be initiated within the first hour of birth. Despite efforts to increase rates of early and exclusive breastfeeding in low- and middle-income countries (LMICs), challenges with uptake remain. This analysis reviews trends in early and exclusive breastfeeding, and the impact of infant feeding interventions in reducing childhood diarrhoea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It has been shown that beginning breastfeeding as soon as possible and continuing it exclusively protects new-born babies against death due to diarrhea ( 43 ). A self-limiting characteristic of the human body that is usually caused by gastroenteritis is termed “diarrhoea.” It is characterized by having loose stools abnormally frequently in a single day ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that beginning breastfeeding as soon as possible and continuing it exclusively protects new-born babies against death due to diarrhea ( 43 ). A self-limiting characteristic of the human body that is usually caused by gastroenteritis is termed “diarrhoea.” It is characterized by having loose stools abnormally frequently in a single day ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adequate timing and characteristics of CF are fundamental for infants worldwide. In low- and middle-income countries, correct CF is closely linked to parents’ and caregivers’ educational level, and it also represents a milestone in infants’ diarrhea and disease prevention [ 4 ]. Moreover, in a review analyzing CF practices in 80 low- and middle-income countries, the authors concluded that monitoring CF indicators across the world and implementing policies and programs to reduce wealth-related inequalities are essential to achieving children’s nutritional standards [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition, vitamin deficiencies, and delayed motor and cognitive development in infants and young children are all health problems that can be further worsened by poor complementary feeding methods, which can also impede a child’s growth [ 18 ]. Inadequate breastfeeding and delayed introduction of complementary foods, increase the risk of childhood mortality and morbidity [ 19 , 20 ]. To prevent child malnutrition and death, breastfeeding must begin within an hour of delivery, be exclusive for the first six months with the introduction of timely and adequate quality complementary food, and last for at least two years [ 21 ].…”
Section: Introductionmentioning
confidence: 99%